Ancient pathogen genomics: insights into timing and adaptation. Issue 79 (February 2015) - Harkins, Kelly M.; Stone, Anne C.
Abstract: Disease is a major cause of natural selection affecting human evolution, whether through a sudden pandemic or persistent morbidity and mortality. Recent contributions in the field of ancient pathogen genomics have advanced our understanding of the antiquity and nature of human-pathogen interactions through time. Technical advancements have facilitated the recovery, enrichment, and high-throughput sequencing of pathogen and parasite DNA from archived and archaeological remains. These time-stamped genomes are crucial for calibrating molecular clocks to infer the timing of evolutionary events, while providing finer-grain resolution to phylogenetic reconstructions and complex biogeographical patterns. Additionally, genome scale data allow better identification of substitutions linked to adaptations of the pathogen to their human hosts. As methodology continues to improve, ancient genomes of humans and their diverse microbiomes from a range of eras and archaeological contexts will enable population-level ancient analyses in the near future and a better understanding of their co-evolutionary history.